152. Applying A Difference-in-Difference Analysis to Assess Effect of Antimicrobial Stewardship Strategies on Changes in Antimicrobial Use. (31st December 2020) - Chou, Ann F; Zhang, Yue; Jones, Makoto M; Graber, Christopher J; Goetz, Matthew B; Madaras-Kelly, Karl; Samore, Matthew H; Glassman, Peter A
Abstract: Background: About 30–50% of inpatient antimicrobial therapy is sub-optimal. Health care facilities have utilized various antimicrobial stewardship (AS) strategies to optimize appropriate antimicrobial use, improve health outcomes, and promote patient safety. However, little evidence exists to assess relationships between AS strategies and antimicrobial use. This study examined the impact of changes in AS strategies on antimicrobial use over time. Methods: This study used data from the Veterans Affairs (VA) Healthcare Analysis & Informatics Group (HAIG) AS survey, administered at 130 VA facilities in 2012 and 2015, and antimicrobial utilization from VA Corporate Data Warehouse. Four AS strategies were examined: having an AS team, feedback mechanism on antimicrobial use, infectious diseases (ID) attending physicians, and clinical pharmacist on wards. Change in AS strategies were computed by taking the difference in the presence of a given strategy in a facility between 2012–2015. The outcome was the difference between antimicrobial use per 1000 patient days in 2012–2013 and 2015–2016. Employing multiple regression analysis, changes in antimicrobial use was estimated as a function of changes in AS strategies, controlling for ID human resources in and organizational complexity. Results: Of the 4 strategies, only change in availability of AS teams had an impact on antimicrobial use. Compared to facilities with no AS teams at both time points, antibiotic use decreased by 63.9 uses per 1000 patient days in facilities that did not have a AS team in 2012 but implemented one in 2015 (p=0.0183). Facilities that had an AS team at both time points decreased use by 62.2 per 1000 patient days (p=0.0324). Conclusion: The findings showed that AS teams reduced inpatient antibiotic use over time. While changes in having feedback on antimicrobial use and clinical pharmacist on wards showed reduced antimicrobial use between 2012–2015, the differences were not statistically significant. These strategies may already be a part of a comprehensive AS program and employed by AS teams. In further development of stewardship programs within healthcare organizations, the association between AS teams and antibiotic use should inform program design and implementation. Disclosures: All Authors : No reported disclosures